Curcuma Pudding as an Effort to Increase Children's Appetite - Rukmaini; Jenny Anna Siauta; Luthfiyah Adegi (International Journal of Community Services, 2024)
Based on the Indonesian Nutritional Status Survey (SSGI), it was found that the prevalence of stunting in toddlers in West Java reached 20.2% in 2022. Stunting stems from the discussion of nutritional status that is not met properly, originating from problems with decreased appetite in children such as difficulty eating. One of the traditional medicines that can increase and improve poor appetite in children is curcuma because it contains the active substance curcumin which can increase the activity of digestive enzymes. This community service aims to prevent an increase in stunting rates and nutritional disorders in children, through curcuma pudding, children's appetite disorders can be overcome in the Bogor Regency area. Providing Health Education about nutritional needs in children and how to overcome eating disorders in children by utilizing natural ingredients. The results of the devotion of parents (mothers) know the nutritional needs of children and can make innovations from natural curcuma ingredients in the form of pudding that children like, with the hope of overcoming appetite disorders in children. Curcuma pudding is useful, cheap, easy to get, and easy to process so mothers can apply it at home and give it to children, especially to increase and overcome appetite disorders in children.